Customizable 3D-printed stirrers for investigation, optimization and scale-up processes of batch emulsion copolymerizations. (12th October 2019) - Bettermann, Sven; Stuhr, Robin; Moritz, Hans-Ulrich; Pauer, Werner
Highlights: Versatile and inexpensive polyamide stirrers were 3D-printed for investigation. First thermal-initiated batch emulsion copolymerizations with 3D-printed stirrers. Scale-manufacturing concept enabled access to customizable and tailor-made stirrers. Successful scale-up with comparable droplet dispersions (±2 nm) for different scales. Online monitoring of mixing characteristics and copolymerizations by inline turbidity. Abstract: Diverse and cost-effective polyamide stirrers, printed by fused deposition modeling, were used in a 0.5 L reaction calorimeter (Mettler Toledo RC1e) to principally investigate the suitability and performance of 3D-printed stirrers. Thermal-initiated batch emulsion copolymerizations of styrene and butyl acrylate were successfully carried out with monomer contents between 20 and 40 wt% and temperatures in the range of 60 to 85 °C. Further, precisely adjusted stirrers were designed and fabricated based on a constant volume related power input for scale-up processes in a 10 L batch reactor. This scale-manufacturing concept enables a time-effective and inexpensive access to versatile and tailor-made 3D-printed stirrers, even for the implementation in already existing reaction systems. Inline turbidity was used as online monitoring tool to detect the mixing characteristics and control the course of emulsion polymerization processes. Analytical results of the 10 L resembled those of the 0.5 L scale and proved our main objective to produce comparable droplet dispersions (±2 nm). The resulting emulsions from 0.5 and 10 L scale were stable with Zeta potential values down to –90 mV. Neither product adhesion on nor deformation of the 3D-printed stirrers were found even at higher temperatures, monomer contents or scale-up processes.